2012
DOI: 10.1038/sj.bdj.2012.1041
|View full text |Cite
|
Sign up to set email alerts
|

A survey of dental hygienists in the United Kingdom in 2011. Part 1 – demographics and working patterns as dental hygienists

Abstract: The results of this study provide a snapshot of the demographics and practice patterns of DHs and DH/Ts in the UK in the summer of 2011. They confirm the results of a survey that was conducted in England in early 2011 and of a survey that took place in Scotland in 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…This is consistent with the research that has been conducted in England 92,114 and highlights the precarious nature of professional work for many DCPs.…”
Section: Attitudes Of Patients and The Nhs Dental Team To Role Substisupporting
confidence: 75%
See 4 more Smart Citations
“…This is consistent with the research that has been conducted in England 92,114 and highlights the precarious nature of professional work for many DCPs.…”
Section: Attitudes Of Patients and The Nhs Dental Team To Role Substisupporting
confidence: 75%
“…This is consistent with the finding that over one-third of these DCP roles worked in more than one practice. Eaton et al 114 found that the mean number of clinical hours worked per week was 24.6 hours. This propensity for part-time working among DCPs is consistent with findings from other studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations